Mixoma en ventrículo derecho: una localización inusual - Tápanes Daumy, Hiram; Peña Fernández, Maylin; Senra Reyes, Lysmara; Naranjo Ugalde, Alfredo M. (CorSalud, 2020)
Mixoma en ventrículo derecho: una localización inusual